FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN KEPUTIHAN PATOLOGIS SISWI SMAN 1 SIMPANG HILIR KABUPATEN KAYONG UTARA - Abrori, Abrori; Hernawan, Andri Dwi; Ermulyadi, Ermulyadi (Unnes Journal of Public Health, 2017)
Vaginal discharge is one of reproductive tract infections that commonly occure among teenage girls. It actually does not need a treatment, but its impact will lead to infertility and cervical cancer. The aim of this study was to determine factors associated with the occurrence of pathologic vaginal discharge among high school girls in Kayong Utara Regency. This study was an analytical obervational research with cross sectional approach. Sampling technique used was simple random sampling. Sample size were 59 respondents. Data were collected by interview using questionnaire. Data analysis was done by chi square test. Results showed that there were significant association between knowledge of vulva hygiene (p=0.036), vaginal cleaning motion (p=0.025), use of vaginal cleanser (p=0.002), tight underwear (p=0.007), and use of public toilets (p=0.021) with pathologic vaginal discharge. There were no significant association between obesity and pathologic vaginal discharge (p=0.587). Factors associated with pathological vaginal discharge were knowledge of vulva hygiene, vaginal cleaning motion, use of vaginal cleanser, use of tight underwear, and use of public toilets.